PENGARUH KEPADATAN TERHADAP PERTUMBUHAN DAN SINTASAN UDANG LITOPENAEUS VANNAMEI PADA KOLAM BUNDAR MENGGUNAKAN SISTEM BIOFLOK: Effect of Density on Growth And Survival of Litopenaeus Vannamei Shrimp in Circle Pond Using Biofloc System - Ahmad Fauzi; Mita Ayu Liliyanti; Hamid Hamid; Denianto Yoga Sativa (Yayasan Al-Amin Qalbu, 2023)
This study aims to determine the effects of stocking density on the growth, survival rate, and the business of feasibility of the white shrimp culture using BFT in cylinder pond. The research method used was an experimental method, with a non-factorial completely randomized design (CRD). Each treatment (5000, 7500, and 10000 shrimp/pond) was repeated 3 (three) times. The observations showed that the growth of absolute weight and length of the 5000 shrimp/pondtreatment gave the best results, 8.82 g (0.13 g / day) and 8.81 cm (0.126 cm / day). However, the analysis of variance indicate that the stocking density of L.vannamei in the range of 5,000 to 10,000 has no significant effect on differences in growth, both weight or length. Stocking density of L.vannamei was detected to give a significant on survival rate. One-way analysis of variance and the Least Significant Difference (LSD) test showed that the stocking density of 5,000 was significantly in their survival on the 7,500 and 10,000 shrimp/pond. Meanwhile, the 7,500 shrimp/pond was not significantly to the 10,000 shrimp/pond. Economically, the stocking difference is a direct consequence of costs and revenues. The results of the business feasibility analysis inform that the three treatments are included in the feasible category for development, and the stocking density of 5000 shrimp/pond provides the best profit